2003
DOI: 10.1002/app.12146
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced corrosion protection coatings prepared from soluble electronically conductive polypyrrole‐clay nanocomposite materials

Abstract: A series of electronically conductive nanocomposite materials that consisted of soluble polypyrrole (PPY) and layered montmorillonite (MMT) clay platelets were prepared by effectively dispersing the inorganic nanolayers of MMT clay in organic PPY matrix via an in situ oxidative polymerization with dodecylbenzene sulfonic acid (DBSA) as dopant. Organic pyrrole monomers were first intercalated into the interlayer regions of organophilic clay hosts and followed by a one-step oxidative polymerization. The as-synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 31 publications
7
88
1
Order By: Relevance
“…According to the published reports on PCN materials, the unparalleled ability of smectite clays was found to boost the thermal stability of polymers. 1,[5][6][7][8][9][10][11][12][13][14][15][16] Evidently, we found that the onset of the thermal decomposition of those PCN materials shifted slightly toward higher temperature range than that of neat ABS, which confirmed the enhancement of intercalated polymers. After ϳ700°C, the curves are all leveled off, and mainly the inorganic residue (e.g., Figure 1 The representative FTIR spectra of (a) neat ABS (b) CLABS1 (c) CLABS3 (d) CLABS5 (e) organophilic clay (f) Na ϩ -clay.…”
Section: Characterizationsupporting
confidence: 84%
See 1 more Smart Citation
“…According to the published reports on PCN materials, the unparalleled ability of smectite clays was found to boost the thermal stability of polymers. 1,[5][6][7][8][9][10][11][12][13][14][15][16] Evidently, we found that the onset of the thermal decomposition of those PCN materials shifted slightly toward higher temperature range than that of neat ABS, which confirmed the enhancement of intercalated polymers. After ϳ700°C, the curves are all leveled off, and mainly the inorganic residue (e.g., Figure 1 The representative FTIR spectra of (a) neat ABS (b) CLABS1 (c) CLABS3 (d) CLABS5 (e) organophilic clay (f) Na ϩ -clay.…”
Section: Characterizationsupporting
confidence: 84%
“…Generally, they combine both the characteristics of the inorganic material and the organic polymer. PCN material is a promising system because the clay possess a high aspect ratio and a platy morphology and can be employed to boost the physical properties (e.g., thermal stability, 1 mechanical strength, 2 fire retardant, 3 gas barrier, 4 and corrosion protection [5][6][7][8][9][10][11][12][13][14][15][16] ) of bulk polymers.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that MMT plays as a good barrier to prevent corrosive species due to the layer structure [8,9,[19][20][21][22]. So MMT will have the same effects for all the samples.…”
Section: Change Of Ocpmentioning
confidence: 99%
“…As a result, corrosion rate decreases. In addition, MMT played a role as a barrier to prevent the corrosive species from steel [8,9,[19][20][21][22]. Consequently, metal should be protected with two effects at the same time, say anion inhibitor and barrier.…”
Section: Change Of Ocpmentioning
confidence: 99%
See 1 more Smart Citation